The action radius of oxytocin release in the mammalian CNS: from single vesicles to behavior - Chini, Bice; Verhage, Matthijs; Grinevich, Valéry (Trends in pharmacological sciences, 2017)
The hypothalamic neuropeptide oxytocin (OT) has attracted the attention both of the scientific community and a general audience because of its prosocial effects in mammals, and OT is now seen as a facilitator of mammalian species propagation. Furthermore, OT is a candidate for the treatment of social deficits in several neuropsychiatric and neurodevelopmental conditions. Despite such possibilities and a long history of studies on OT behavioral effects, the mechanisms of OT actions in the brain remain poorly understood. In the present review, based on anatomical, biochemical, electrophysiological, and behavioral studies, we propose a novel model of local OT actions in the central nervous system (CNS) via focused axonal release, which initiates intracellular signaling cascades in specific OT-sensitive neuronal populations and coordinated brain region-specific behaviors.